Penatalaksanaan Komprehensif pada Wanita Usia 30 Tahun dengan Demam Tifoid melalui Pendekatan Kedokteran Keluarga di Wilayah Kerja Puskesmas Kemiling - Nadhila Nur Shafitha; Fitria Saftarina (CV. Jasa Sukses Abadi, 2022)
Typhoid fever is a global infectious disease, especially in developing countries. Typhoid fever in Indonesia is endemic and is a public health problem. Failure of therapy by using antibiotics can bind closely to the patient, and germs. To implement comprehensive and holistic family doctor services by identifying risk factors, clinical problems, and patient management based on evidence based medicine with strategies that are patient centered, family oriented and community oriented. The analysis of this study is a case report. Primary data were obtained through history taking (autoanamnesis), physical examination, supporting examination and home visits. Assessment is carried out based on a holistic diagnosis of the initial, process, and final study quantitatively and qualitatively. Patient Mrs. H, 40 years old, came to the clinic with complaints of fever accompanied by headache, abdominal pain, nausea, vomiting, and a dirty tongue. Patients diagnosed with typhoid fever are in accordance with evidence based medicine. After the intervention, there was a decrease in clinical symptoms, an increase in knowledge and changes in the behavior of patients and their families. The diagnosis and management of typhoid fever in this patient was in accordance with national guidelines. Changes in clinical symptoms, knowledge and behavior in patients and their families after interventions based on evidence based medicine that are patient centered and family approach